Hubungan Kekuatan Otot Lengan dan Daya Ledak Otot Tungkai dengan Ketepatan Smash Dalam Permainan Bolavoli Pada Tim Putri Kabupaten Halmahera Barat - Pribadi, Mahatma Raison; Akhmady, Alief Lam (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the relationship between arm muscle strength and leg muscle explosive power with smash accuracy in volleyball games in the Halbar Regency women's team. This study uses a correlational design. The subjects of this study were the Halbar Regency women's volleyball team, which consisted of 34 athletes. Data analysis used the Pearson product-moment correlation formula and multiple correlation at a significance level of α = 0.05. The findings in this study indicate that: 1) the calculated t-value is -0.719 and the significance value is 0.475 which is greater than α 0.05, so it can be stated that there is no relationship between arm muscle strength and volleyball smash accuracy, 2) the calculated t-value is 3.777 and the significance value is 0.001 which is smaller than α 0.05, so it can be stated that there is a relationship between leg muscle explosive power and volleyball smash accuracy and 3) the calculated F-value is 17.896 > F-table value of 3.3048, so it can be stated that there is a relationship between arm muscle strength and leg muscle explosive power and volleyball smash accuracy. The conclusions are as follows: 1) There is no relationship between arm muscle strength and smash accuracy in volleyball games in the Halbar Regency women's team, 2) There is leg muscle explosive power and smash accuracy in volleyball games in the Halbar Regency women's team, and 3) There is a joint relationship between arm muscle strength and leg muscle explosive power with smash accuracy in volleyball games in the Halbar Regency women's team